Litigation services handbook : the role of the financial expert - Weil, Roman L.; Lentz, Daniel G.; Hoffman, David P. (Hoboken, New Jersey : John Wiley & Sons, Inc., 2012)
"A comprehensive reference for financial experts engaged in litigation services, the lawyers who engage them, and the litigants who ultimately benefit from the efforts of both groups, Litigation Services Handbook, Fifth Edition is referred to as the litigation "bible." With nearly fifty chapters reading like a who's who in law and accounting, the handbook includes all aspects of litigation services, including current environments, the process itself, a wealth of cases, how to prove damages, and practical considerations of court appearances"--
pt. 1. The litigation environment -- pt. 2. Developing a damages analysis -- pt. 3. Litigation tools and techniques -- pt. 4. Ancillary issues in damages matters -- pt. 5. Civil litigation -- pt. 6. Criminal matters and investigations -- pt. 7. Family law.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Forensic accounting -- United States; Evidence, Expert -- United States; LAW -- Civil Procedure; Evidence, Expert; Forensic accounting; United States; Electronic books